Le minoranze greche in Calabria meridionale e nel Salento - Aprile, Marcello (Linguistik Online, 2025)
Within the Italo-Romance linguistic space, there are two Greek communities: one is the Southern Calabrian minority, which resides in the province of Reggio Calabria, and the other is the Grico minority, which is to be found in the province of Lecce. This paper aims to reconstruct the profile of the two Greek linguistic minorities in Italy, examining several key issues: origins, demographics and linguistic space, written and oral literature, and tools (dictionaries and linguistic writings). Moreover, a basic linguistic profile of Western Greek is drawn, addressing key issues of phonetics, morphology, syntax, lexicon, and semantics.